Exploring the patients' experiences of living with a subcutaneous implantable cardioverter defibrillator. (1st December 2018) - Forman, Jacqueline; Baumbusch, Jennifer; Jackson, Heather; Lindenberg, Jen; Shook, Alyssa; Bashir, Jamil
Abstract: Background: The implantable cardioverter defibrillator provides effective treatment for the prevention of sudden cardiac arrest but significant risks associated with transvenous implantation persist. The subcutaneous implantable cardioverter defibrillator has proven to be an alternative and innovative treatment option for select patients to mitigate these risks. Obtaining the patients' perspectives can provide clinicians with essential information to guide implant selection, procedural decision-making, and support patient management. Conventional implantable cardioverter defibrillator patients have reported shock-related anxiety, fear, insufficient education, and challenges adapting to physical and psychological changes. Little evidence exists to determine whether differences between the subcutaneous implantable cardioverter defibrillator and conventional implantable cardioverter defibrillator allow for the transferability of our current knowledge to the care and management of this population. Aims: The purpose of this study was to explore patients' experiences of living with a subcutaneous implantable cardioverter defibrillator including the decision-making process, implant, and follow-up care processes. Methods: Using an exploratory qualitative approach, semi-structured interviews were conducted by telephone with 15 participants who underwent subcutaneous implantable cardioverter defibrillator implant. Results: Analysis revealed five main themes: (a) influences on decision-making; (b) unmet education needs; (c) physical impact; (d) psychological impact; and (e) recommendations. Conclusion: As a new technology, little knowledge of the subcutaneous implantable cardioverter defibrillator exists outside of the tertiary implanting sites, therefore developing new strategies to increase learning and dissemination is essential. Although similarities exist in our findings to those of conventional implantable cardioverter defibrillators, there are significant differences in the decision-making process and physical impact which require individualized care planning and development of strategies to provide a patient-centered approach to care.